PENGARUH PERILAKU KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASA DAN KINERJA PEGAWAI PEMERINTAH KABUPATEN SINJAI - Abd Karim (Jurnal Ilmiah Administrasita', 2016)
These research aims to analysis the direct effect of transformational leadership, transactional leadership and compensation toward satisfaction, to analysis the direct effect of transformational leadership, transactional leadership and compensation toward performance, to analysis the satisfaction toward performance in direct effect, and to analysis the indirect effect of transformational leadership, transactional leadership and compensation toward performance through satisfaction. The research applied in Regional Government Sinjai Regency with total sample as amount 200 respondent based on Slovin formulation. Data from questioner to analysis with Structural Equation Model used of AMOS 18 computer programs. The result of research to found the transformational leadership in direct have positive and insignificant affected toward satisfaction. That mean the transformational leadership which oriented on vision, mision, expect, intelegence and attention have applied, unless insignificant to sufficient of satisfaction by employee. The transformational leadership in direct have positive and insignificant toward performance. The transformation leadership which applied cannot achieve of performance in maximal as well as through input, process, output and outcome. The transformational leadership indirect have positive and insignificant toward performance through satisfaction. That mean the transformational leadership cannot sufficient of satisfaction and increasing of performance, so insignificant indirect it. Compensation in direct have positive and significant toward performance. That mean the compensation it by employee as the esteem which get contribution in increasing of performance suitable of input, proses, output and outcome.